2006
DOI: 10.1073/pnas.0600633103
|View full text |Cite
|
Sign up to set email alerts
|

The Phycomyces madA gene encodes a blue-light photoreceptor for phototropism and other light responses

Abstract: Phycomyces blakesleeanus is a filamentous zygomycete fungus that produces striking elongated single cells that extend up to 10 cm into the air, with each such sporangiophore supporting a sphere containing the spores for dispersal. This organism has served as a model for the detection of environmental signals as diverse as light, chemicals, touch, wind, gravity, and adjacent objects. In particular, sporangiophore growth is regulated by light, and it exhibits phototropism by bending toward near-UV and blue wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 58 publications
4
129
1
6
Order By: Relevance
“…Strains with mutations in madA or madB had a mild defect in light-dependent cryA mRNA accumulation. Similar mild effects on photoactivation of transcription have been observed for other Phycomyces genes and are probably due to the high intensity of light that is applied and to the fact that none of them is a complete knockout (31,32). However, the double mutant strains did not show any accumulation of cryA mRNA after light exposure (Fig.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Strains with mutations in madA or madB had a mild defect in light-dependent cryA mRNA accumulation. Similar mild effects on photoactivation of transcription have been observed for other Phycomyces genes and are probably due to the high intensity of light that is applied and to the fact that none of them is a complete knockout (31,32). However, the double mutant strains did not show any accumulation of cryA mRNA after light exposure (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…The perception of light in Phycomyces requires the products of the madA and madB genes that interact to form a photoreceptor complex (31,32). Strains with mutations in madA or madB had a mild defect in light-dependent cryA mRNA accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WC proteins have been well characterized in the filamentous ascomycete Neurospora crassa (Ballario et al, 1996;Linden and Macino, 1997;Froehlich et al, 2002;He et al, 2002), and homologues have been identified in ascomycetes, basidiomycetes, and zygomycetes (for review, see Corrochano, 2007). For example, Phycomyces blakesleeanus mutants defective in blue-light-dependent phototrophism may contain mutations in the madA gene, which encodes a protein similar to WC-1 of N. crassa (Idnurm et al, 2006). Inactivation of a wc-1 homologue in the human pathogen Cryptococcus neoformans results in a blind phenotype (Idnurm and Heitman, 2005;Lu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The WC-2 protein contains a zinc-finger and 1 PAS domain (17), and interacts with WC-1 to form a complex that binds to the promoters of light-inducible genes, presumably to activate their transcription (13,18,19). WC proteins are required for the responses to blue light in the basidiomycete fungi Cryptococcus neoformans (20,21) and Coprinus cinereus (22), and 3 wc-1 genes have been described in the zygomycetes Rhizopus oryzae and Mucor circinelloides (23,24). A Mucor WC-1 protein is modified by ubiquitylation, presumably to regulate its activity (25).…”
mentioning
confidence: 99%